RELIABILITY OF THE DATA ON MORBIDITY AND MORTALITY FROM MUSCULOSKELETAL SYSTEM DISEASES IN RESIDENTS OF THE TULA REGION - David Sh Vaisman; V N Sorotskaya; Roland M Balabanova (Научно-практическая ревматология)
Diseases of the musculoskeletal system (DMSS) are a topical social, medical, and economic problem. They are widespread and account for about 10% of the overall morbidity and primary disability of population, about 5% of primary morbidity, and about 0.1% of mortality. The reliable statistics are important to analyze the situation and make necessary adjustments to the organization of medical care.Objective. To examine the accuracy of the data on morbidity and mortality from DMSS in the Tula region.Materials and Methods. Data from statistical reports, reference documents, and databases of Tula region residents (including those who died in 2000–2011) were used.Results. The inequality in growth rates of general and primary morbidity were revealed, which is indicative of incorrect coding and underestimation of DMSS in medical organizations of the Tula region.A comprehensive phased statistical study was carried out to assess validity of the mortality data, including the following: verification of databases for errors using an automated system; control of postmortal diagnosis quality using the four-digit subcategory code in accordance with the WHO recommendations; analysis according to the initial and multiple causes of death. Underestimation of mortality from rheumatoid arthritis by about 25% was revealed. Attention was paid to the implementation and use of automated systems.